2018
DOI: 10.1016/j.impact.2017.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Grouping concept for metal and metal oxide nanomaterials with regard to their ecotoxicological effects on algae, daphnids and fish embryos

Abstract: Manufactured nanomaterials (NMs) are being developed in many different variations such as size, shape, crystalline structure and surface modifications. To avoid the testing of each single nanomaterial variation, grouping and read-across strategies for nanomaterials similar to classical chemicals are discussed. Grouping and read-across aim to identify NM groups with analogous sets of properties or properties that enable reasonable predictions of a NM hazard without additional testing. This will contribute to sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(60 citation statements)
references
References 37 publications
1
57
0
Order By: Relevance
“…Regarding the selected endpoints for read-across, none of the case studies available in Table 3 consider REACH-relevant endpoints 5 . A case study recently published by Hund-Rinke et al (2018) where metal and metal oxide NMs are grouped for aquatic toxicity according to ion release, morphology, and reactivity, takes finally into consideration a REACH-relevant endpoint. This aspect conflicts with the grouping frameworks study reported in Tables 1 and 2, where hazard data are related to animal studies and to apical endpoints.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the selected endpoints for read-across, none of the case studies available in Table 3 consider REACH-relevant endpoints 5 . A case study recently published by Hund-Rinke et al (2018) where metal and metal oxide NMs are grouped for aquatic toxicity according to ion release, morphology, and reactivity, takes finally into consideration a REACH-relevant endpoint. This aspect conflicts with the grouping frameworks study reported in Tables 1 and 2, where hazard data are related to animal studies and to apical endpoints.…”
Section: Discussionmentioning
confidence: 99%
“…A different approach for ecotoxicity was proposed by Hund-Rinke et al (2018) where metal and metal oxide NMs are grouped according to three properties that were considered relevant: ion release, morphology, and reactivity. PC characterisation of NMs is provided in the paper (surface chemistry, surface area, crystalline structure, morphology, primary particle size, hydrodynamic diameter, zeta potential, isoelectric point, and solubility rate).…”
Section: Application Of Computational Tools In Grouping For Read-acromentioning
confidence: 99%
“…The physical chemical characteristics of the nanoforms, preparation of suspensions, the performance of characterisation, and ecotoxicological tests with algae and daphnids as well as the investigation of the attachment of nanoforms to the green algae R. subcapitata are described in [8,9]. In addition, for ionic silver and nanosilver data on the ecotoxicity on D. subspicatus were included as data for these forms were not generated with algae in the underlying projects [14].…”
Section: Information Basis For Approaching Grouping Hypothesesmentioning
confidence: 99%
“…All data generated or analysed during this study are included in the published articles [8][9][10]14] and their additional information files.…”
Section: Abbreviationsmentioning
confidence: 99%
See 1 more Smart Citation